COMPARISON OF SAMPLING TECHNIQUES FOR ISOTOPIC ANALYSIS OF SHALLOW MARINE CARBONATES - Psomiadis, D.; Dotsika, E.; Albanakis, K.; Zisi, N.; Poutoukis, D.; Lazaridis, A. (Bulletin of the Geological Society of Greece, 2010)
Recent studies have widely used beachrock samples for isotopic and dating techniques; however the source matrix of the analyzed samples varied. Bulk rock material, skeletal fragments, allochems and pure cement have been used in different studies. Basic parameters of each technique are crucial for the accuracy and the reliability of the obtained results, affecting each time important agents. This study includes isotopic analyses (δ13C, δ18O) of marine carbonates (beachrocks) from the coasts of N. Greece (Thassos island). The sub-sampling was carried out along beachrock cores, following different procedures and protocols. The obtained results show in general expecting differences in isotopic composition of the samples. Experiments that included heating of the samples show an influence on oxygen isotope. Different separation and selection of sampling material affect majorly the isotope of carbon (13C). Differences are attributed to the origin of the carbonate component of the analyzed material. The study indicates that a full-range of comparison experiments should be implemented in order to define in detail the analytical parameters that affect isotopic measurements. The results of that kind of studies will be used not only in stable isotope analyses but also in a variety of methods used in palaeoclimatic and palaeoenvironmental research.